An Indonesian Child Learning Sentence Construction - Djonhar, Santi Chairaini (Journal of ELT Research, 2016)
This study investigates the language acquisition of an Indonesian child (a boy, aged 6 years) who learns and uses English (in Indonesia/Jakarta) inside and outside the classroom. This child regularly watches his favorite English movies such as Disney Channel and Nickelodeon from cable TV, and he frequently communicates in English at home, particularly with his only younger brother and mother. The data were collected for 18 months by recording his spontaneous speech. The data were transcribed then analyzed to see the development of his English syntactic constructions: i.e. infinitival and sentential complements. These types of constructions are chosen to investigate since it is not always easy for EFL learners to learn these constructions. The findings of this study show that the development of these constructions is enormous: the process of his learning English can be similar (if not the same) to that of English Children. It is because this child and the English children basically share common principles (sufficient exposure to and practices of English) of learning the language.